Visualization study on oil retention and flow characteristics of R32/PVE oil in suction lines with different flow orientations. (August 2022) - Zeng, Weijie; Zhang, Zhiting; Hu, Jinting; Gu, Bo; Tian, Zhen
Highlights: Oil retention amount of R32 with PVE oil in compressor suction lines were measured experimentally. The flow patterns of R32/PVE were observed and the flow mechanism was analyzed. Horizontal, vertical upward and two inclination pipes were included to investigate the influence of flow configuration. The existing horizontal flow pattern maps and WWF correlations were not compatible with the flow patterns of R32-PVE mixture. The effects of mass flux, oil mass fraction and flow orientation on oil retention were discussed. Abstract: Oil retention characteristic and flow patterns of R32/PVE lubricant oil mixture in compressor suction lines were investigated. Smooth copper tubes with 10.7mm inner diameter and four tube orientations including horizontal flow, vertical upward flow and inclined upward flow with 45 ° and 60 ° inclined angles, were utilized as test samples. Saturation temperature and superheat degree were maintained at 7.5 ° C and 12 ° C, respectively. The operation conditions of refrigerant mass flux and nominal oil mass fraction covered ranges of 48.5−230 kgm −2 s −1 and 1−5%, respectively. The oil retention amount was measured by the remove and weight technique. Based on the visualization technique, flow patterns of R32/oil mixture were also observed, identified and analyzed. The characteristic of flow patterns was greatly influenced by the thermophysical properties of refrigerant-oil mixture. Comparisons of existing flow pattern maps and wet wall fraction correlations were conduct to investigate the applicability. The experimental result showed that oil retention in suction lines increased with the decrease in refrigerant mass flux and increase in oil mass fraction. The oil retention amount of 60 ° inclination suction line was slightly higher than that for 45 ° . Additionally, the difference of oil retention among the four configurations becomes limited at high mass flux conditions.